Divergent trajectories of ocean warming and acidification. (14th December 2021) - Mortenson, Eric; Lenton, Andrew; Shadwick, Elizabeth H; Trull, Thomas W; Chamberlain, Matthew A; Zhang, Xuebin
Abstract: The ocean provides a major sink for anthropogenic heat and carbon. This sink results in ocean changes through the dual stressors of warming and acidification which can negatively impact the health of the marine ecosystem. Projecting the ocean's future uptake is essential to understand and adapt to further climate change and its impact on the ocean. Historical ocean uptake of heat and CO2 are tightly correlated, but here we show the trajectories diverge over the 21st century. This divergence occurs regionally, increasing over time, resulting from the unique combination of physical and chemical drivers. We explored this relationship using a high-resolution ocean model and a 'business as usual' CO2 emission pathway, and demonstrate that the regional variability in the carbon-to-heat uptake ratios is more pronounced than for the subsequent carbon-to-heat storage (change in inventory) ratios, with a range of a factor of 30 (6) in heat-to-carbon uptake (storage) ratios among the defined regions. The regional differences in heat and carbon trajectories result in coherent regional patterns for sea surface warming and acidification by the end of this century. Relative to the mean global change (MGC) at the sea surface of 2.55 °C warming and a decrease of 0.32 in pH, the North Pacific will exceed the MGC for both warming and acidification, the Southern Ocean for acidification only, and the tropics and midlatitude northern hemisphere will exceed MGC only for warming. Regionally, mapping the ocean warming and acidification informs where the marine environment will experience larger changes in one or both. Globally, the projected ocean uptake of anthropogenic heat and carbon informs the degree to which the ocean can continue to serve as a sink for both into the future.